2001
DOI: 10.1099/00207713-51-4-1235
|View full text |Cite
|
Sign up to set email alerts
|

Flavobacterium frigidarium sp. nov., an aerobic, psychrophilic, xylanolytic and laminarinolytic bacterium from Antarctica.

Abstract: A psychrophilic, aerobic bacterium designated A2iT was isolated from marine sediment recovered from shallow waters surrounding Adelaide Island, Antarctica (67S 34' S, 68S 07' W). The organism exhibited xylanolytic and laminarinolytic activity and was halotolerant. Basic characterization showed that it was Gram-negative, non-motile, yellow-pigmented ( β,β-carotene-3,3'-diol) and positive for oxidase and catalase synthesis. Analysis of the 16S rDNA sequence suggests that the organism belongs to the Flexibacter-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(53 citation statements)
references
References 31 publications
0
52
0
Order By: Relevance
“…Therefore, distribution of this aromatic amine was newly analyzed within the 71 species (111 strains), except for the species located in the class Bacteroides, in which 2-phenylethylamine had not been determined (Hamana and Nakagawa, 2001a, b). Furthermore polyamines of 6 newly validated species (7 strains) belonging to the two new genera Zobellia (Barbeyron et al, 2001) and Tenacibaculum (Suzuki et al, 2001) and new three psychrophilic Flavobacterium species (Humphry et al, 2001;Tamaki et al, 2003;Zhu et al, 2003) of the family Flavobacteriaceae, and a species of the genus Dyadobacter (Chelius and Triplett, 2000) of the family Flexibacteraceae were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, distribution of this aromatic amine was newly analyzed within the 71 species (111 strains), except for the species located in the class Bacteroides, in which 2-phenylethylamine had not been determined (Hamana and Nakagawa, 2001a, b). Furthermore polyamines of 6 newly validated species (7 strains) belonging to the two new genera Zobellia (Barbeyron et al, 2001) and Tenacibaculum (Suzuki et al, 2001) and new three psychrophilic Flavobacterium species (Humphry et al, 2001;Tamaki et al, 2003;Zhu et al, 2003) of the family Flavobacteriaceae, and a species of the genus Dyadobacter (Chelius and Triplett, 2000) of the family Flexibacteraceae were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…The primary structures of plant cell wall hydrolases from P. cellulosa and C. mixtus are very similar (9,13,19), suggesting that there is an evolutionary link between these two prokaryotes. To investigate this possible relationship, the 16S rRNA genes of the two organisms were amplified by PCR by using primers which bind to the 5Ј and 3Ј ends of eubacterial 16S ribosomal DNA (15), and the genes were sequenced. The data showed that the two sequences exhibited 95% sequence identity, indicating that the two bacteria could be classified in the same genus but are different species.…”
mentioning
confidence: 99%
“…The strains of the genus Flavobacterium are known for their specialized roles in the uptake and degradation of the high-molecular-mass fraction of dissolved organic matter and in remineralization processes, both in freshwater and in marine ecosystems (McCammon and Bowman, 2000). They have been frequently reported in oligotrophic and eutrophic Antarctic freshwater, terrestrial samples, and marine sediments, suggesting their wide diffusion in Antarctica and their ecological roles in macromolecule hydrolysis (McCammon et al, 1998;McCammon and Bowman, 2000;Humphry et al, 2001;Van Trappen et al, 2003Yi et al, 2005;Yi and Chun, 2006;Michaud et al, 2012).…”
Section: Discussionmentioning
confidence: 99%